Membangun Sistem Pembinaan Narapidana Korupsi Di Indonesia - Dwinanda Linchia Levi Heningdyah Nikolas Kusumawardhani (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2023)
Corruption in Indonesia has mushroomed in various sectors. To anticipate the growth of corruption crimes, proper handling is needed. This paper will discuss the problems of the system for fostering corruption convicts that are already running in Indonesia, as well as how to build an ideal system for fostering corruption convicts in Indonesia in dealing with corruption convicts in the future. One of the strategies used is to use the right pattern of coaching for corruption convicts. In order to achieve effective development of corruption convicts, concrete steps are needed in the form of efforts to reconstruct it in three aspects at once, namely institutional reconstruction (a linking institution is needed between institutions in the criminal justice system), system reconstruction, especially legal provisions starting from the investigations up to the coaching stage in Correctional Institutions, as well as cultural reconstruction, namely the culture of synchronism for all stakeholders in uniting the spirit of eradicating corruption at all levels.